An Exploratory Study of the Influence of Load and Practice on Segmental and Articulatory Variability in Children with Speech Sound Disorders - Vuolo, Janet (Clin Linguist Phon, 2016)
This exploratory treatment study used phonetic transcription and speech kinematics to examine changes in segmental and articulatory variability. Nine children, ages 4- to 8-years-old, served as participants, including two with childhood apraxia of speech (CAS), five with speech sound disorder (SSD), and two who were typically developing (TD). Children practised producing agent + action phrases in an imitation task (low linguistic load) and a retrieval task (high linguistic load) over five sessions. In the imitation task in session one, both participants with CAS showed high degrees of segmental and articulatory variability. After five sessions, imitation practice resulted in increased articulatory variability for five participants. Retrieval practice resulted in decreased articulatory variability in three participants with SSD. These results suggest that short-term speech production practice in rote imitation disrupts articulatory control in children with and without CAS. In contrast, tasks that require linguistic processing may scaffold learning for children with SSD but not CAS.